MODERNITY IN THE MANAGEMENT OF THE UMSU FACULTY OF ISLAMIC STUDIES - Rambe, Syahril; Dasopang, Erwin Pinayung; Pahutar, Masrawati; Ariadin, Imran; Qorib, Muhammad (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
This study aims to analyze student achievement and innovation, analyze the efficiency of using technology in Islamic religious education learning programs at FAI UMSU, and analyze the readiness of FAI UMSU in the activities of the Go International KKN program. This study uses qualitative research methods with field study designs, and data collection interview techniques with an unstructured approach. The researcher himself acts as a key instrument. Data analysis using approach domain analysis and content analysis and checking the validity of the data using triangulation techniques. The results of the study are 1) the level of achievement and innovation of FAI UMSU students in the field of Islamic religious education learning programs has experienced good development. Student innovation has also experienced maximum development such as being able to create a corpse bath prop that has received IPR, 2) the level of efficiency in the use of technology in Islamic religious education learning programs at FAI UMSU has been utilized to the fullest, and 3) Readiness of FAI UMSU in implementing the KKN program Go International has been well programmed and runs optimally through cooperation in the form of MoUs from several ASEAN-level countries.